Teknik dan Prosedur Analisis Mimpi, Transferensi, dan Resistensi dalam Bingkai Teori Konseling Psikoanalisis - Habsy, Bakhrudin All; Saputra, Fanzha Erza Nanda; Choirunisa, Lia; Maulidiyah, Nuris Saidah Rahmah (TSAQOFAH, 2024)
The psychoanalysis theory is a theory which is an attempt to explain the nature and development of the human personality. The theory assumes that personalities develop when there are conflicts of these psychological aspects, which generally occur in children or younger age, psychoanalysis has much to offer for education. Some of the techniques employed in this psychoanalytic sigmund Freud theory include dream analysis, analysis and interpretation of transference and analysis and interpretation of resistance. The goal of analyzing Sigmund Freud's theory is to help us learn about the techniques used in psychoanalysis counseling. The results of this study include (1) understanding psychoanalysis counseling, (2) purposes of psychoanalysis counseling, (3) dream analysis techniques, (4) transference analysis and interpretation, (5) analysis and interpretation of resistance, (6) the merits and deficiency of psychoanalysis counseling.